Occupational exposure to lead: a review of the literature (Research, Society and Development, 2023)
Lead is considered a metal that man learned to use around 4000 BC. for the manufacture of domestic utensils. Today, this practice is no longer used due to the metal causing toxicity to the human body. For this reason, the objective was to carry out a literature review on the risks of exposure to lead in workers exposed to this element. An integrative literature review was carried out from 2014 to 2022, in LILACS, MEDLINE, SCIELO, ResearchGate and ScienceDirect® databases. Inclusion criteria were literature published in Portuguese and English available in full and free of charge, the stipulated period from 2014 to 2022, and paid and duplicate literature excluded. 12 literatures were selected, 66.6% (8) of which are in English and 33.4% (4) are in Spanish. The methodological processes present in the literature are 66.6% (8) literature review, 8.4% (1) cross-sectional and observational study, and 25.0% (3) experimental studies. Occupational exposure to lead for workers generates possible toxicities in the body, such as anorexia, gastritis and acute headaches. Therefore, toxicological tests are necessary to quantify and diagnose this metal in this context, the pharmacist can act in actions towards diagnosis, monitoring, prevention, remediation and studies that help society in important decision-making associated with the presence of this chemical element in people and in contexts that can facilitate contamination.